2007
DOI: 10.1038/sj.embor.7400955
|View full text |Cite
|
Sign up to set email alerts
|

Human INT6/eIF3e is required for nonsense‐mediated mRNA decay

Abstract: The mammalian integration site 6 (INT6) protein has been implicated in breast carcinogenesis and characterized as the eIF3e non-core subunit of the translation initiation factor eIF3, but its role in this complex is not known. Here, we show that INT6 knockdown by RNA interference strongly inhibits nonsensemediated messenger RNA decay (NMD), which triggers degradation of mRNAs with premature stop codons. In contrast to the eIF3b core subunit, which is required for both NMD and general translation, INT6 is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…NMD assays with HeLa cells with the GlNS39 and GlWT constructs were performed as described previously (47), and mRNAs were measured by quantitative reverse transcription-PCR (qRT-PCR) using the QuantiTect SYBR green qRT-PCR kit (Qiagen) and ␤-globin primers. Similarly, for the analysis of GADD45␣, SLIT2, BAG1, ATF4, and MAP3K14 mRNA half-lives, total RNA was extracted by using the Nucleospin RNA kit (Macherey-Nagel).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMD assays with HeLa cells with the GlNS39 and GlWT constructs were performed as described previously (47), and mRNAs were measured by quantitative reverse transcription-PCR (qRT-PCR) using the QuantiTect SYBR green qRT-PCR kit (Qiagen) and ␤-globin primers. Similarly, for the analysis of GADD45␣, SLIT2, BAG1, ATF4, and MAP3K14 mRNA half-lives, total RNA was extracted by using the Nucleospin RNA kit (Macherey-Nagel).…”
Section: Methodsmentioning
confidence: 99%
“…In mammalian cells, the silencing of INT6 seems to marginally affect general translation, but evidence for a role of INT6 in the translation of specific genes was recently obtained (26,67). Regarding its role in association with eIF3, we have previously shown that INT6 was important for the degradation of cellular mRNAs by nonsensemediated mRNA decay (NMD) (47). The latter is a quality control process leading to the degradation of mRNAs, including a premature stop codon (PTC), which can arise from mutation or aberrant alternative splicing and eventually prevents the synthesis of a truncated protein, which could serve as a dominant negative protein against an intact protein (3).…”
mentioning
confidence: 99%
“…Thus, the phosphorylation status of Upf1 was assessed with a phospho-(Ser) ATM/ATX substrate antibody after immunoprecipitation of Upf1 (49,50). As shown in Fig.…”
Section: Pata Enhances the Interaction Of Upf1 With Other Components mentioning
confidence: 99%
“…For plasmids and siRNA transfections, the amount of FCS used in the culture medium was reduced to 5%, and antibiotics were omitted for siRNA transfection, which was performed using the Lipofectamine 2000 reagent according to the manufacturer's instructions (Invitrogen). siRNA duplexes I6.1, I6.3, I6.4, and anti-EIF3B have been described previously (Morris and Jalinot 2005;Morris et al 2007). For endogenous histone labeling experiments, a Luc siRNA duplex was used.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%